Analysis of nutritional status and needs of 10th-grade high school students - I Kadek Eka Putra Yasa; Hendra Mashuri; I Komang Sukarata Adnyana (Sriwijaya Journal of Sport, 2025)
Research Problems: In Indonesia, nutritional problems, including those in adolescent children, are increasing yearly. Research Objectives: This research aims to analyse the nutritional status and needs of class X.2 students at SMAS Karya Wisata Singaraja. Methods: This type of research is quantitative descriptive research using survey methods. This research was carried out by measuring and calculating students' nutritional status through the Body Mass Index according to Age (BMI/A). Then classify the nutritional status of students into the categories of mild thinness, severe thinning, ideal, mild obesity and severe obesity.  Results: Based on the research results, the nutritional status and needs of students were obtained, several students had not reached optimal nutritional status. Of the total 26 people in the mildly underweight category, there were 9 people (35%), 2 people in the severely underweight category (8%), 11 people in the normal category (42%), 3 people in the mild obesity category (11%), and 1 person in the severe obesity category (4%). Meanwhile, for macro nutritional needs, the average carbohydrate nutritional requirement for students is 431 grams, the average protein requirement is 80 grams, and the average fat requirement is 108 grams. Conclusion: The nutritional status of students showed that there were still some students who had not reached optimal nutritional status. So, there needs to be treatment from PE teachers giving additional movement tasks and parental support in providing adequate nutritional intake.